Companions of the Peace : diaries and letters of Monica Storrs, 1931-1939 - Storrs, Monica, 1888-1967.; Fast, Vera K., 1929- (Toronto ; Buffalo : University of Toronto Press, 1999)
"In 1929 a cultured English gentlewoman arrived in the barely settled wilderness of northern British Columbia as an Anglican missionary, intending to assuage her sense of duty by staying for one year. She stayed for twenty-one. The years covered by Monica Storrs's journal entries (1931-9) were at times unbearably hard, the depression compounding what was already a demanding existence. She and the group of women she lived with, the Companions of the Peace, were sent out as 'missionaries of empire.' As the journals progress, Storrs's droll British wit persists but her imperialistic attitude softens as her work draws her into the lives around her. Expanding on the initial mandate to start Sunday schools, foster contact with women, and perform church services, she became involved in assembling libraries, lending money for seed grain, financing medical assistance, and organizing theatrical performances and poetry contests. After her death even the non-British inhabitants of the Peace River district described her as 'one of us.'"--Jacket
Contents -- Acknowledgments -- Introduction -- Diaries and Letters, 1931â€?1939 -- Postscript -- Notes -- Photo Credits -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- R -- S -- T -- U -- V -- W -- Map -- Illustrations
Includes bibliographical references (pages 203-235) and index.
JSTOR
Keywords: Storrs, Monica, -- 1888-1967 -- Diaries; Storrs, Monica, -- 1888-1967 -- Correspondence; Anglican Church of Canada -- Biography; Storrs, Monica, -- 1888-1967 -- Journal intime; Storrs, Monica, -- 1888-1967 -- Correspondance; Companions of the Peace; Église épiscopale du Canada -- Biographies; Storrs, Monica, -- 1888-1967; Anglican Church of Canada; Peace River Valley (B.C. and Alta.) -- Social life and customs; Frontier and pioneer life -- Peace River Valley (B.C. and Alta.); Pioneers -- Peace River Valley (B.C. and Alta.) -- Diaries; Pioneers -- Peace River Valley (B.C. and Alta.) -- Correspondence; Women pioneers -- Peace River Valley (B.C. and Alta.) -- Diaries; Women pioneers -- Peace River Valley (B.C. and Alta.) -- Correspondence; Vie des pionniers -- Colombie-Britannique -- Peace River-Liard.; Peace River-Liard (C.-B.) -- Histoire; Paix, Vallée de la rivière de la (C.-B. et Alb.) -- Mœurs et coutumes; Pionniers -- Paix, Vallée de la rivière de la (C.-B. et Alb.) -- Journaux intimes; Pionniers -- Paix, Vallée de la rivière de la (C.-B. et Alb.) -- Correspondance; Pionnières -- Paix, Vallée de la rivière de la (C.-B. et Alb.) -- Journaux intimes; Pionnières -- Paix, Vallée de la rivière de la (C.-B. et Alb.) -- Correspondance; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Canada -- General; BIOGRAPHY & AUTOBIOGRAPHY -- Women; Frontier and pioneer life; Manners and customs; Pioneers; Women pioneers; Canada -- Peace River Valley; Electronic books; Biographies; Diaries; Personal correspondence